The effect of deep learning and problem based learning on active and independent learning with mediation variable - Tamami, Fauziyah Qurrota A'yun; Shohib, Muhammad Wildan; Maksum, Muh. Nur Rochim; Rabbi, Md. Fajlay; Daud, Zainor; Fadli, Nazar; Wadi, Munshid Falih (Journal of Research in Instructional, 2025)
This study aims to analyze the influence of deep learning (DL) and problem based learning (PBL) on the active and independent learning of students with the mediation variable of self-regulated learning (SRL) at high school in Surakarta. The research method used was an explanatory quantitative approach with data collection through a closed questionnaire distributed to 157 students in grades X and XI. Data were analyzed using the structural equation modeling (SEM) approach SmartPLS 4.0 software. The analysis stage includes evaluating the measurement model (outer model) by testing convergent validity (AVE). Furthermore, the structural model (inner model) was analyzed by testing the path coefficient and significance using the bootstrapping method. Hypothesis testing was carried out with the ho rejection criterion if the p-value was < 0.05 and the t-statistic > 1.96. The results of the study show that deep learning and problem based learning have a significant effect on active and independent learning, both directly and through the mediation of self-regulated learning. All study variables met the criteria for validity and reliability, as indicated by AVE and Cronbach's alpha values above 0.5 and 0.7. The model fit index (SRMR = 0.089, and NFI = 0.931) confirms the fit of the proposed model. The results show that deep learning and problem based learning significantly affect active and independent learning through self-regulated learning strategies and are capable of enhancing students’ active involvement and independence in learning process.